2016
DOI: 10.1063/1.4953662
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of chimera and cluster states in a minimal globally coupled network

Abstract: A "chimera state" is a dynamical pattern that occurs in a network of coupled identical oscillators when the symmetry of the oscillator population is broken into synchronous and asynchronous parts. We report the experimental observation of chimera and cluster states in a network of four globally coupled chaotic optoelectronic oscillators. This is the minimal network that can support chimera states, and our study provides new insight into the fundamental mechanisms underlying their formation. We use a unified ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
105
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(110 citation statements)
references
References 35 publications
2
105
0
3
Order By: Relevance
“…First, it has been observed that these states can exist in small networks of as few as 4 phase oscillators [27][28][29][30] and also in the model of semiconductor lasers [31]. Experimentally, chimera states of this type have been recently observed in small networks of optoelectronic oscillators [32] as well as coupled pendula [33,34].In the Letter, we show that the weak chimera patterns which are characterized by two frequency synchronized oscillators and one evolving with different frequency can be observed in the networks of 3 identical nodes. As the proof of the concept we use a network of Kuramoto oscillators with inertia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, it has been observed that these states can exist in small networks of as few as 4 phase oscillators [27][28][29][30] and also in the model of semiconductor lasers [31]. Experimentally, chimera states of this type have been recently observed in small networks of optoelectronic oscillators [32] as well as coupled pendula [33,34].In the Letter, we show that the weak chimera patterns which are characterized by two frequency synchronized oscillators and one evolving with different frequency can be observed in the networks of 3 identical nodes. As the proof of the concept we use a network of Kuramoto oscillators with inertia.…”
mentioning
confidence: 99%
“…First, it has been observed that these states can exist in small networks of as few as 4 phase oscillators [27][28][29][30] and also in the model of semiconductor lasers [31]. Experimentally, chimera states of this type have been recently observed in small networks of optoelectronic oscillators [32] as well as coupled pendula [33,34].…”
mentioning
confidence: 99%
“…Отметим, что шести генераторов оказывается достаточно для возник-новения состояния " химера". Как было недавно показано в работе [13], состояния " химера" могут существовать в ансамблях, состоящих всего лишь из четырех идентичных осцилляторов.…”
Section: рис 3 (продолжение)unclassified
“…Состояния " химера" были сначала обнаружены в ансамблях фазовых осцилляторов, связь между которыми является локальной [6], нелокаль-ной [5] или глобальной [7], а затем и в ансамблях, элементы которых не являются фазовыми осцилляторами [8][9][10]. Состояния " химера" были обнаружены не только при теоретических, но и при экспериментальных исследованиях [11][12][13].…”
unclassified
“…Chimera states were first discovered in ensembles of phase oscillators with local [6], nonlocal [5], or global coupling [7] and then also found in ensembles with elements not representing phase oscillators [8][9][10]. Chimeras were not only theoretically predicted, but also observed in experimental investigations [11][12][13].…”
mentioning
confidence: 97%